The consequences of drug-nutrient interaction in the treatment of hospital patients: a systematic review (Research, Society and Development, 2023)
Drug-food interactions are defined as changes in the pharmacokinetics or pharmacodynamics of a drug or nutritional element or an impairment of nutritional status as a result of the addition of a drug. Drug interaction becomes a worrying cause of morbidity worldwide, as it is especially important in cancer patients, as they are often using polypharmacy, and there may be interactions between the drugs and the chemotherapeutic agents used. This descriptive study is a systematic literature review, whose objective was, through already published scientific studies, to gather scientific information for the contribution and construction of the proposed theme. In this way, several studies were evaluated that brought suitable proposals for the elaboration of research on the analysis of the drug-nutrient interaction. The research was carried out in the period December 2022, using articles from 2007 to 2022 as a time frame, through an online search of articles indexed in the databases of the PubMed Database of U.S. platform. National Library of Medicine (PUBMED), Scientific Electronic Library Online (SCIELO) and Google Scholar. Drug interactions are more common in day-to-day activities than health professionals might assume. Knowledge on the subject can also help reduce cases. The multidisciplinary work between pharmacists, nurses, doctors and nutritionists can contribute satisfactorily so that the prevention and resolution of possible interactions between food and drugs can actually occur, in order to favor the quality of the patient's health.